A preliminary study in Wistar rats with enniatin A contaminated feed. (March 2014) - Manyes, Lara; Escrivá, Laura; Serrano, Ana Belén; Rodríguez-Carrasco, Yelko; Tolosa, Josefa; Meca, Giuseppe; Font, Guillermina
Abstract A 28-day repeated dose preliminary assay, using enniatin A naturally contaminated feed through microbial fermentation by a Fusarium tricinctum strain, was carried out employing 2-month-old female Wistar rats as in vivo experimental model. In order to simulate a physiological test of a toxic compound naturally produced by fungi, five treated animals were fed during 28 days with fermented feed. As control group, five rats were fed with standard feed. At the 28th day, blood samples were collected for biochemical analysis and the gastrointestinal tract, liver and kidneys were removed from each rat for enniatin A detection and quantitation. Digesta were collected from stomach, duodenum, jejunum, ileum and colon. Enniatin A present in organs and in biological fluids was analyzed by liquid chromatography-diode array detector (LC-DAD) and confirmed by LC-mass spectrometry linear ion trap (MS-LIT); also several serum biochemical parameters and a histological analysis of the duodenal tract were performed. No adverse effects were found in any treated rat at the enniatin A concentration (20.91 mg/kg bw/day) tested during the 28-day experiment. Enniatin A quantitation in biological fluids ranged from 1.50 to 9.00 mg/kg, whereas in the gastrointestinal organs the enniatin A concentration ranged from 2.50 to 23.00 mg/kg. The high enniatin A concentration found in jejunum liquid and tissue points to them as an absorption area. Finally, two enniatin A degradation products were identified in duodenum, jejunum and colon content, probably produced by gut microflora.